Interferência de diferentes sais sobre a cultura starter de salame tipo italiano - Fieira, Claudia (2014)
The meat has high nutritional value, is sensitive to spoilage microorganisms due to high amount of free water and favorable pH, being necessary to use the traditional techniques of drying, salting and fermentation, thus, processed foods end up being sources of sodium. The partial replacement of salt is questioned because it can come cause interference in the development of micro-organisms responsible for the characteristics of the product, flavor, aroma, texture, among others, so it is necessary to check that the replacement entails on starter cultures used, and consequently on food security. The purpose of this study was to verify the influence of the salts: KCl, MgCl2, CaCl2, used to partially replace sodium chloride on the starter culture added as technological manufacturing facility and determine the physico-chemical, microbiological and sensory properties. The Italian salami were produced, performed physical-chemical and microbiological analyzes as well as a sensory test with hedonic scale and texture profile. Cultures starters conferred standards of quality and desirable identity. Salts did not interfere in this process. The product with reduced sodium chloride showed sensory acceptability among hedonic terms like slightly and like moderately (6-7) and was in accordance with the applicable legal standards. In addition to presenting reduction in sodium content of approximately 16, 32 and 43% .